Financing the low-carbon transition in Europe - Olimpia Carradori; Margherita Giuzio; Sujit Kapadia; Dilyara Salakhova; Katia Vozian (European Central Bank (ECB), 2023)
Using evidence from the EU emissions trading system, we collect verified emissions of close to 4000 highly polluting and mostly non-listed firms responsible for 26% of EU's emissions. Over the period 2013-2019, we find a non-linear relationship between leverage and emissions. A firm with higher leverage has lower emissions in subsequent years. However, when leverage exceeds 50%, a further increase is associated with higher emissions. Our difference-in-differences approach sheds light on the existence of a group of firms that are too indebted to successfully accomplish the low-carbon transition, even when they face a steep increase in the cost of their emissions.
Keywords: C58; E58; G32; Q51; Q56; Q58; 330; low-carbon transition; climate change; debt finance; transition finance; EU ETS